The Rhetoric of Forgiveness Versus The Desire For Revenge: The Role of Religious Speeches in Peace Building in Indonesia - Peter Suwarno (Asia-Pacific Journal on Religion and Society, 2018)
The purpose of this paper is to discuss the rhetoric of forgiveness and the desire for revenge, including the advantages and disadvantages of both in life and interaction between humans, and in the effort to resolve conflicts and create peace. The study in this paper is based largely on literature research, observing religious interactions, and collecting notes and records of religious speeches in Indonesia. In addition to examining the controversy that covers the usefulness of forgiveness and the benefits of the desire for revenge, this paper would like to show that forgiveness is far more beneficial than the desire for revenge, especially in a conflict-prone plural society like Indonesia.